In Situ Growth of Plasmonic Gold Nanoparticles for the Direct and Sensitive Colorimetric Assay of Glucose. (9th February 2017) - Weng, Shaohuang; Feng, Feng; Guo, Honghui; Wu, Namei; Zheng, Yanjie; Lin, Zhen; Lin, Xinhua
Abstract : Gold nanoparticles (Au NPs)‐based colorimetric assay for the highly sensitive and selective detection of glucose has been conducted. The sensing, which was based on the in situ growth of Au NPs in the presence of glucose, was developed with the solution changing from colorless to red. This change could be observed with the naked eye or a ultraviolet–visible (UV–vis) spectrophotometer. Moreover, adding trace amounts of Tween‐20 kept Au NPs well spaced. Under the optimal assay conditions, the absorbance of Au NPs at 550 nm was proportional to glucose concentration within 400–1800 μM with a linear regression equation, and the detection limit was 6.28 μM. Some common interfering compounds in beverages, including other sugars, food additives, and amino acids, did not affect glucose sensing. Therefore, the proposed Au NP‐based colorimetric assay could be successfully used to determine glucose in beverages. Abstract : Highly sensitive and selective detection of glucose through naked eyes can be obtained through simple gold nanoparticles‐based colorimetric assay.